PENERAPAN ARSITEKTUR VERNAKULAR PADA RANCANGAN MUSEUM SEJARAH DAN BUDAYA DI KABUPATEN TOLITOLI - Ahwal; Ali, Moh. Mudassir (ANALOGI : Arsitektur, Lingkungan Binaan & Planologi, 2024)
This study aims to design the Tolitoli Regency History and Culture Museum with a vernacular architectural approach, which integrates local cultural elements into the building design. Through qualitative methods, data were collected through interviews, field observations, and literature studies on Tolitoli traditional architecture. The results of the study indicate that the application of local materials such as ironwood and bamboo, as well as the design of a gable roof and natural ventilation, creates a building that is sustainable and adaptive to local climate conditions. In addition, the integration of traditional carving motifs into the interior of the museum strengthens cultural identity and increases the educational value of the building. The museum is designed as a multifunctional social space, acting as a center for cultural and community interaction. With a vernacular architectural approach, this museum not only functions as a place to preserve historical artifacts, but also as a symbol of dynamic and sustainable local identity. The results of this study are expected to be a model for the development of architecture that prioritizes sustainability and cultural preservation in other regions. Overall, this discussion underlines the importance of a vernacular architectural approach in the design of public buildings such as museums. In addition to producing aesthetic and functional designs, this approach is also able to create strong cultural ties, support environmental sustainability, and provide a positive impact on the tourism sector and the regional economy.